Mechanisms of service ecosystem emergence: Exploring the case of public sector digital transformation - Simmonds Hamish; Gazley Aaron; Kaartemo Valtteri; Renton Michelle; Hooper Vai (Elsevier, 2025)
This research extends literature on the emergence of service ecosystems by developing new theoretical insight and explanation into how service ecosystems experience change and stability over time. Empirically, our case study focuses on digital transformation in the New Zealand public sector and the enterprise services market in 2010–2017. The exploratory and illustrative study builds on 22 in-depth interviews and extensive document analysis. We reveal three key mechanisms of service ecosystem emergence: compression, ecotonal coupling, and refraction. These mechanisms contribute to overcoming conflationary theorizing and the value of emergence in service research by establishing emergent relationality and a processual intertwining of being and becoming. These become the basis of multi-levelled, multidimensional complexity and cumulative organizing. We conclude the work by discussing the paper’s contribution to service research.